1996
DOI: 10.1128/jvi.70.9.5845-5851.1996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a naturally occurring mutation in the hepatitis B virus basal core promoter on precore gene expression and viral replication

Abstract: The basal core promoter (BCP) of hepatitis B virus (HBV) controls the transcription of both the precore RNA and the core RNA. The precore RNA codes for the secreted e antigen, while the core RNA codes for the major core protein and the DNA polymerase and also is the pregenomic RNA. The double mutation of nucleotides 1762 and 1764 in the BCP from A and G to T and A, respectively, is frequently observed in HBV sequences isolated from chronic patients. Several papers have reported conflicting results regarding wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
242
6
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(259 citation statements)
references
References 43 publications
(51 reference statements)
10
242
6
1
Order By: Relevance
“…Mutations in the core promoter and precore region have been shown to decrease or abolish HBeAg production. 10,11 The polymerase protein functions as a reverse transcriptase as well as a DNA polymerase. The X protein is a potent transactivator and may play a role in hepatocarcinogenesis.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…Mutations in the core promoter and precore region have been shown to decrease or abolish HBeAg production. 10,11 The polymerase protein functions as a reverse transcriptase as well as a DNA polymerase. The X protein is a potent transactivator and may play a role in hepatocarcinogenesis.…”
Section: Hepatitis B Virusmentioning
confidence: 99%
“…[41][42][43][44] Some of these mutations confer enhanced replication. [45][46][47][48][49][50] Additionally, mutations in the surface gene have been implicated in some cases of FH B. 51 Therefore, a number of viral mutations and/or host factors likely are involved in the pathogenesis of FH.…”
Section: Clinical-pathologic Features Of Hbeag-negative Variantsmentioning
confidence: 99%
“…The BCP mutations when engineered into an infectious clone were associated with an increase in virion production. 34,35 Other mutations that created novel transcription factor binding sites in promoter or enhancer regions also had a high replication yield phenotype. 30 However, other groups have shown that while the BCP mutations were associated with reduced HBeAg production, there was no significant effect on the amount of intracellular preS1/PreS2/S proteins or PreS/S messenger RNA transcripts.…”
Section: Functional Studies: Phenotype Assessment and Replication Fitmentioning
confidence: 99%